2009
DOI: 10.1016/j.reprotox.2008.11.001
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between birth weight, gestational age and perfluorooctanoic acid (PFOA)-contaminated public drinking water

Abstract: Background-Recent studies have examined the associations between perfluorooctanoic acid (PFOA) levels in cord blood and maternal plasma with lowered birth weight and gestational age in humans; however, no study has examined these effects in a population of known high PFOA exposure. Residents drinking PFOA-contaminated water from the Little Hocking Water Association (LHWA) in Washington County, Ohio have serum PFOA levels approximately 80 times those in the general U.S. population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
64
2
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 47 publications
4
64
2
1
Order By: Relevance
“…As for PFOS, we also found in subgroup analyses comprising native Swedish women higher levels in term than in preterm newborns. This is not in accordance with other studies where no significant associations were found for gestational age (Apelberg et al 2007a, b;Fei et al 2007;Nolan et al 2009). However, a new study by Chen et al (2012) found an inverse association between PFOS levels and gestational age.…”
contrasting
confidence: 85%
See 1 more Smart Citation
“…As for PFOS, we also found in subgroup analyses comprising native Swedish women higher levels in term than in preterm newborns. This is not in accordance with other studies where no significant associations were found for gestational age (Apelberg et al 2007a, b;Fei et al 2007;Nolan et al 2009). However, a new study by Chen et al (2012) found an inverse association between PFOS levels and gestational age.…”
contrasting
confidence: 85%
“…2007;Apelberg et al 2007b;Washino et al 2009). The findings on the effect of infant sex (Inoue et al 2004;Apelberg et al 2007b) and gestational age (Apelberg et al 2007a, b;Nolan et al 2009) on the levels of PFCs are limited. Many of those studies on the determinants have contradicting results.…”
Section: Introductionmentioning
confidence: 99%
“…Serum PFOA concentrations were found to be positively associated with the amount of tap water consumed (Emmett et al, 2006). However, consumption of PFOA-contaminated water was not found to be associated with adverse effects on birth weight, gestational age, congenital anomalies, labor/delivery complications, and other maternal risk factors (Nolan et al, 2009(Nolan et al, , 2010. The findings that PFOA concentrations were not associated with adverse consequences on birth weight contradict data reported in a birth cohort in Denmark (Fei et al, 2007) and Baltimore, MD (Apelberg et al, 2007).…”
mentioning
confidence: 66%
“…No association was seen between elevated PFOA exposure and pregnancy outcomes, including miscarriage, stillbirth or birth defects, lowered birth weight [288,289], but for some suggestion of early preterm birth and possibly fetal growth restriction [290]. No association of PFOA with birth defects was found but further investigation was recommended for the brain [291].…”
Section: More Exposed Populationsmentioning
confidence: 97%